Techniques of Cryopreservation for Ovarian Tissue and Whole Ovary - Amir Arav; Pasquale Patrizio (SAGE Publishing, 2019)
Cryopreservation of ovarian tissue has been considered experimental for many years, but very recently the American Society of Reproductive Medicine is reviewing the process and perhaps soon will remove the label of "experimental" and recognize it as an established method for preserving female fertility when gonadotoxic treatments cannot be delayed or in patients before puberty or when there is desire to cryopreserve more than just few oocytes. This article discusses in detail the 3 methodologies used for cryopreservation: (a) slow freezing, (b) directional freezing, and (c) vitrification.